PP.24.21: EVALUATION OF PLACENTAL AND FETAL DEVELOPMENT IN STROKE-PRONE SPONTANEOUSLY HYPERTENSIVE RATS. (June 2015) - Barrientos, G.; Uceda, A.; Toblli, J.E.
Abstract : Objective: Arterial hypertension (HT) affects 1–5% of pregnant women worldwide, with a rising prevalence due to increasing maternal age, obesity, and type 2 diabetes. Pregnancies complicated by HT increase the risk of superimposed preeclampsia, fetal growth restriction (FGR), preterm delivery, and perinatal death. So far, there is scarce information available on placental development and function in severe HT animal models such as the Stroke-Prone Spontaneously Hypertensive Rat (SHRSP) strain. Thus, the present study was conducted in order to characterize pregnancy in the SHRSP focusing on the impact of blood pressure changes on placental development and fetal growth. Design and method: SHRSP and Wistar Kyoto (WKY) females (10–12 weeks old, N = 5animals/day analysed) were mated to congenic males and checked daily for vaginal plugs, denoted as gestation day (GD) 1. Blood pressure (BP) was determined by the tail-cuff method pre-mating and on the morning of GD1, 7, 9, 13, 17 and 19. On the selected dates, females were housed in metabolic cages for collection of 24 h urine samples. Following collection of blood samples, animals were euthanized and implantation sites isolated for morphological analyses. Fetal and placental weights were recorded on GD 18 and GD 20. Results: Pregnant SHRSP remained hypertensive throughout the course of the experiment. While BP in WKY females showed slight variations, both SBP and DBP rose in SHRSP, peaking on GD13 and returning to pre-pregnancy levels at term (GD19, results shown in Table 1). Compared to WKY, SHRSP displayed an impaired fertility (noted by decreased pregnancy rates) and signs of placental insufficiency (i.e., decreased F/P weight ratios) and FGR on GD18 and 20. Morphological alterations were evident in SHRSP term placentas, including a decreased fractional area occupied by the junctional zone layer and thickened walls of the maternal vessels irrigating the labyrinth. Figure. No caption available. Conclusions: SHRSP presented significant alterations in fetal growth probably due to defective placental development and function linked to the hypertensive scenario. Moreover, SHRSP showed signs of altered renal function near term. These findings together suggest that SHRSP may be a useful model for further studies on pathogenic mechanisms in hypertensive pregnancies.